Stunting Prevention Efforts in Rowobranten Village, Kendal: Integration of Monitoring Toddler Growth and Development and Providing PMT - Muhammad Ainun Na’im; Risma Nafakhatus Sakhariyah; Fazsya Tatra Khalia (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Stunting is a significant health problem in Rowobranten Village, Kendal, which has an impact on children's physical growth and cognitive development. This research aims to analyze efforts to overcome stunting through the integration of monitoring the growth and development of toddlers and providing additional food (PMT). The method used involves collecting primary data from monitoring activities at posyandu as well as distribution of PMT to pregnant women and toddlers. The research results show that routine monitoring of toddler growth and development accompanied by nutritional intervention through PMT is effective in reducing the prevalence of stunting. In conclusion, this integrative approach can be an effective intervention model for reducing stunting at the village level. Further recommendations include increasing public awareness about the importance of balanced nutrition and ongoing training for health cadres.